An investigation of written communication in the curriculum of entrepreneurship education in Malaysian vocational colleges - Hamidah Mohamad (Kulliyyah of Education, International Islamic University Malaysia, 2020)
Entrepreneurship curriculum has been implemented in recent years in Malaysian vocational colleges as a platform to expose school leavers to entrepreneurship skills and provide them the basic know-how needed to engage in an entrepreneurial career. Among this knowledge is written communication which involves the skill of preparing the necessary documents and correspondence in a start-up business. However, research findings indicate that very little is known about Malaysian vocational college graduates' competency in this area after completing the entrepreneurship course. Moreover, existing studies show significant weaknesses or a lack of competency in communication skills, including writing among our graduates. This study aims to explore the implementation of written communication component taught in the entrepreneurship course in Malaysian vocational colleges by examining its curriculum content, teaching approaches and students' perception towards their learning experience. The study applied the mixed method approach, whereby the semi-structured interview and document analysis methods were employed to gather qualitative data, while a semi-structured survey questionnaire was utilised to gather quantitative data. Under qualitative data collection, 15 instructors from 10 vocational colleges located throughout Peninsula Malaysia participated in the interviews. Meanwhile, the document analysis included description, modules and assessments of the entrepreneurship course. The quantitative data collection involved 79 out of 100 participants from 2 vocational colleges in Klang Valley, after which the data were analysed using SPSS, Version 22. The results revealed that the business plan model is applied to form the fundamental structure of written communication component in the entrepreneurship course. However, several key challenges were found in its implementation, including the inconsistency in the key focus point of the syllabus within the written communication knowledge area i.e. between forming the business profile and objective, developing product description and establishing correct financial statements. Additionally, short and inconsistent course delivery period, untrained and unspecialized instructors in the field of entrepreneurship and limitations in facilities and funding were also identified as barriers to effective implementation of the target knowledge as well as the course in general.